In vitro Study of the Antibacterial Activity of Bioactive Glass-ceramic Scaffolds - Gorriti, Marta Fabiana (2009)
Staphylococcus aureus is an opportunistic pathogen of major clinical interest for its high prevalence in biomaterial-related infections. This experimental study provides the first evidence in vitro that bioactive glass-ceramic scaffolds made from both 45S5 Bioglass® and from boron containing bioactive glass (45S5.2B) as well as their ionic dissolution products do no exhibit antibacterial effect against several strains of S. aureus.